Epidemiological aspects of tick-borne diseases in wild and domestic animals of two environmental protection areas in the city of Natal, Rio Grande do Norte State, Brazil - Lopes, Marcos Gomes (2016)
The aim of this study was to determine the serologic and molecular occurrence of Rickettsia spp., Ehrlichia spp., Babesia spp. and Hepatozoon spp. in ticks and domestic and wild animals from two conservation units in the city of Natal, Rio Grande do Norte State, Brazil. The collection period was between October 2012 and August 2013. Serum samples were tested against Rickettsia spp. antigens and Ehrlichia canis by Indirect fluorescent antibody test. Tissue samples and ticks were processed for molecular detection of the pathogens. Twenty-seven marsupials and four rodents were captured, and up to three animals of each species were euthanized. In addition, serum samples from 155 domestic animals: 53 cats living inside the units, 29 dogs domiciled around the areas and 73 dgos of the Zoonosis Control Center of the City (ZCC). Twenty dogs from ZCC were also euthanized and samples of spleen were obtained. Antibodies to at least one of the Rickettsia species tested were detected in six Didelphis albiventris and in one Rattus rattus; 17% (17/102) of the dogs presented antibodies to E. canis and 13% (20/155) of all tested domestic animals (dogs and cats) were seropositive for Rickettsia spp. antigens. Three species of ticks (Amblyomma auricularium, Ixodes loricatus and Ornithodoros mimon) were collected and one A. auricularium was positive for Rickettsia amblyommii by PCR. Two D. albiventris spleen samples amplified PCR products for Ehrlichia spp. Spleen samples from three D. albiventris and spleen and lung sample from one Necromys lasiurus were positive for Babesia spp. by PCR test. Among the 20 spleen samples from dogs subjected to molecular analysis, eight were positive by PCR for E. canis and two for H. canis